Factors associated with the choice of plant and animal science as a career among technical and vocational education post-secondary graduates in Nepal - Chaurasia, Jay; Jaishi, Mahesh; Khanal, Santosh; Poudel, Balika; Ghimirey, Vivek; Acharya, Nobel (Frontiers in Sociology, 2025)
IntroductionThe present study was conducted in 2024 to analyze factors affecting the career preferences of post-secondary graduates in Nepal. The factors that impact the career decisions of secondary school agricultural graduates still need to be more adequately realized.MethodsIn this context, the study was designed as an ex-post-facto research. Graduates of three secondary institutions in Sindhupalchok who participated in the Technical and Vocational Education (TVE) program responded to the questionnaire. Participants were asked to rate their sociodemographic information, preferred profession, and influences on their career decisions using a 5-point Likert scale for specific occupational and personal characteristics. Factor analysis was conducted on the variables using IBM SPSS Statistics 26 Version.ResultsCronbach's alpha coefficients (0.73) were calculated to estimate the reliability of the factor scores. In addition, exploratory factor analysis determined that the sample size selected for this study was sufficient (KMO value of 0.590 exceeded the minimum threshold of 0.50, and Bartlett's chi-square value of 619.447; p < 0.01). Five factors were identified by utilizing maximum likelihood methods with Promax rotation; collectively, these factors accounted for 59.56% of the total variance. Five determinants impacted the career preferences of the participants: personal characteristics, academic accomplishments, physical surroundings, social factors, and economic conditions. The findings indicated that foreign employment ranked highest among all professions with an overall priority of 0.044. Additionally, the findings unveiled that factors such as a conducive learning environment (4.45), workplace quality (4.22), job security (4.20), future employment prospects (3.99), and workplace (4.13) exerted the greatest impact on the career preferences of post-secondary graduates.DiscussionThe expertise and commitment demonstrated by employees are highly valued by employers. The practical workshop procedures also fosters reflection on strategies to enhance creativity and genuine enthusiasm for the profession. A quality workplace encompasses components such as rewards, recognition, and a culture that strongly fosters individuals' professional growth.ConclusionThrough the early involvement of students in the process of selecting a career path, it is possible that enthusiasm and job satisfaction for that particular career preference could be enhanced.